2022
DOI: 10.3390/nu14122366
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Ultra-Processed Food Consumption and Risk of Diabetes Mellitus: A Mini-Review

Abstract: Studying the factors that cause diabetes and conducting clinical trials has become a priority, particularly raising awareness of the dangers of the disease and how to overcome it. Diet habits are one of the most important risks that must be understood and carefully applied to reduce the risk of diabetes. Nowadays, consuming enough home-cooked food has become a challenge, particularly with modern life performance, pushing people to use processed foods. Ultra-processed food (UPF) consumption has grown dramatical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2023
2023
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 47 publications
0
8
0
2
Order By: Relevance
“…Study participants would generally have had discussions with their medical practitioners in an attempt to understand the cause of the disease and may have tried to identify a specific cause for their own illness. The association between food consumption and the emerging non communicable diseases is widely reported in the literature [ 41 43 ]. For example, high consumption of fats especially trans-fats and saturates are commonly implicated in the cause of insulin resistance, glucose intolerance and poor diabetes health outcomes [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Study participants would generally have had discussions with their medical practitioners in an attempt to understand the cause of the disease and may have tried to identify a specific cause for their own illness. The association between food consumption and the emerging non communicable diseases is widely reported in the literature [ 41 43 ]. For example, high consumption of fats especially trans-fats and saturates are commonly implicated in the cause of insulin resistance, glucose intolerance and poor diabetes health outcomes [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Understanding and effectively implementing dietary habits is essential to reducing the risk of developing diabetes. A study on the relationship between ultra-processed food (UPF) consumption and T2DM reported that high consumption of ultra-processed food could increase the risk of developing T2DM in adult individuals and gestational diabetes in women [ 30 ]. In the current study, 37.22% of respondents claimed to consume processed food frequently.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in obesity and T2DM is partly related to a progressively ageing population, adoption of a more sedentary lifestyle and consumption of high energy processed foods. 5 In keeping with this, the prevalence of osteoporosis and fragility bone fractures is also rising. 6 More notably, obesity and diabetes independently increase bone fracture risk, linked to impairments in bone turnover and a detrimental alteration of bone microarchitecture.…”
Section: Introductionmentioning
confidence: 94%